Exceptions to the duty to notify the seller of a non-conformity of the delivered goods in international sales law - Fišer-Šobot, Sandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
Breach of the duty to notify the seller of the lack of conformity of the delivered goods is followed by harsh consequences for the buyer. Namelly, he loses the right to rely on the non-conformity of the goods if he does not give the notice to the seller in adequate and timely manner. In international sales law the buyer is entitled to rely on the lack of conformity of the goods even when he fails to notify the seller in two specific cases. First, if the lack of conformity relates to the facts of which the seller knew or could not have been unaware and which he did not disclose to the buyer. And secondly, the buyer retains remedies for the nonconforming delivery if he has a reasonable excuse for his failure to give the required notice.